Kebijakan Pengaturan Pengelolaan Limbah Alat Peraga Kampanye berdasarkan Prinsip Keberlanjutan Lingkungan Hidup - Ashari, Amalia Nuril; Fitri, Icha Cahyaning (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
This research is motivated by environmental problems caused by campaign props (APK) waste that is not properly managed after election campaigns end. Current regulations focus only on the installation and removal of APK but do not comprehensively address waste management. The purpose of this study is to analyze how APK waste management policies can align with environmental sustainability principles, as well as how election organizers and Bawaslu can support more environmentally friendly campaigns. This study uses normative legal research methods with statutory and conceptual approaches. The findings indicate that stricter and more synchronized policies are needed between election regulations and environmental regulations, including the application of reduce, reuse, recycle (3R) principles, the use of environmentally friendly campaign materials, as well as education and sanctions for election participants. The implications of this study are expected to encourage improvements in regulation and collaboration between institutions so that election campaigns not only uphold democratic principles but also support environmental sustainability.